POLA PENGUPAHAN KARYAWAN TOKO KETIKA LIBUR DI PASAR BATUSANGKAR - Fadilla Rahayu; Nofialdi Nofialdi (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2023)
The main problem in this thesis is that there are differences in the wages of shop employees when they are on vacation at Batusangkar Market. The purpose of this study is to explain the pattern of wages for store employees during holidays at Batusangkar Market and the reasons that are considered as wages at Batusangkar Market. This type of research is field research. This research method is qualitative and describes the pattern of wages for store employees during holidays at Batusangkar Market. Data collection techniques through interviews totaling 9 people. The data that the author has obtained is analyzed by collecting and collecting data on the practice of wages paying store employees during holidays and consideration of wages at the Batusangkar Market. Read, understand, and analyze the data obtained or collected. After the data is collected, arranged, and clarified properly then conclude. The data that has been processed is then analyzed with the fiqh muamalah theory. The results of this study are the pattern of wages for store employees when they are on vacation at Batusangkar Market, namely, wages are deducted and the time when wages are received is postponed. Wages were deducted because the shops were empty of buyers and the time for receiving wages was postponed because that was the system in the market. Wages are paid weekly in cash with a nominal value of Rp. 250,000 – Rp. 300,000. The shop owner does not give all employees any vacation time. Regarding wages being cut and some having postponed the time to receive their wages while there was no vacation allowance at all, some employees felt annoyed and had to accept it because they needed a job and had no other choice to meet their daily needs. Judging from the muamalah fiqh, the wage transaction that occurs in the Batusangkar market has not fulfilled the ijarah requirements because of compulsion from one of the parties and has not paid attention to the principles of justice and eligibility of wages in Islam.